Peran Detasemen Gegana Satuan Brimob Polda Sumatera Utara Dalam Penanggulangan Tindak Pidana Terorisme - Ghofur Hidayat; Triono Eddy; Alpi Sahari (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The eradication of criminal acts of terrorism in Indonesia is very intensively carried out due to the threat of terror, causing many casualties and public unrest at the strata of society. Therefore the government issued various regulations to overcome the criminal acts of terrorism. The eradication of the crime of terrorism certainly requires facilities and infrastructure, one of which is the bomb disposal unit. A detachment of the Gegana Brimob Bomb disposal unit is tasked with defusing bombs which are usually used by terrorists in carrying out their actions. This paper aims to analyze or examine the role of the North Sumatra Regional Police Mobile Brigade Detachment in the handling of terrorism crimes and the obstacles experienced by the North Sumatra Police Mobile Brigade Detachment in dealing with terrorism crime. The results of this study indicate that the role of the Police Mobile Brigade Corps Gegagana is carried out by bomb disposal which is carried out through the stages of preparation, implementation, and consolidation. The barriers experienced by the North Sumatra Regional Police Mobile Brigade Detachment Unit consisted of several internal and external factors.